Dft Approaches to Transport Calculations in Magnetic Single-Molecule Devices - Aravena-Ponce, D; Aravena-Ponce, D (Springer New York LLC, 2016)
Electron transport properties of single-molecule devices based on the [Fe(tzpy)2(NCS)2] complex placed between two gold electrodes have been explored using three different atomistic DFT methods. This kind of single-molecule devices is quite appealing because they can present magnetoresistance effects at room temperature. The three employed computational approaches are: (i) self-consistent non-equilibrium Green functions (NEGF) with periodic models that can be described as the most accurate between the state-of-art methods, and two non-self-consistent NEGF approaches using either periodic or non-periodic description of the electrodes (ii and iii). The analysis of the transmission spectra obtained with the three methods indicates that they provide similar qualitative results. To obtain a reasonable agreement with the experimental data, it is mandatory to employ density functionals beyond the commonly employed GGA (i.e., hybrid functionals) or to include on-site corrections for the Coulomb repulsion (GGA+U method). © 2016, Springer-Verlag Berlin Heidelberg.